Sekolah Perempuan dan Hutan Mangrove: Transformasi Peran Perempuan Waropen Papua dalam Pembangunan Berkelanjutan - Indra Kertati; Christine DW; Selvina Y.Imbiri; Arifa Kohinoor Jadida (MIMBAR ADMINISTRASI FISIP UNTAG Semarang, 2025)
Mangroves are tropical coastal ecosystems that play a vital role in climate change mitigation, ecosystem service provision, and supporting the livelihoods of local communities. However, over the past five decades, the world has lost nearly one-third of its mangrove forests due to land conversion, coastal development, and overexploitation. In Papua, Waropen represents one of the regions with extensive mangrove coverage while simultaneously facing ecological degradation pressures. This study aims to examine the role of Waropen women in mangrove management, particularly following the Women’s School (Sekoper Waropen) initiative launched in 2018, which graduated its first cohort in 2019. The research employed a descriptive qualitative approach, relying on secondary data from government reports, scholarly publications, and media documentation. Thematic analysis was conducted to identify changes in women’s social, economic, and ecological roles post-Sekoper. The findings reveal a significant transformation in women’s roles. Prior to Sekoper, women were mostly confined to subsistence use of mangrove resources for household consumption and had limited involvement in public forums. After participating in Sekoper, women became more engaged in mangrove rehabilitation, village decision-making processes, and economic ventures such as mangrove-based food and beverage products, including crab dishes and mangrove fruit syrup. The program also enhanced women’s environmental literacy, self-confidence, and social recognition as agents of change. Nevertheless, challenges remain, including limited access to capital, technology, and policy support. This study highlights the importance of gender mainstreaming in coastal ecosystem governance and offers recommendations to strengthen women’s role as key actors in sustainable development.